Elastic Electron Scattering Form Factors and Charge Densities for Some Nuclei in 2s-1d Shell Using the Effect of Occupation Numbers - Z. Majeed, Wasan; R. Ridha, Arkan (Iraqi Journal of Science, 2023)
Elastic electron scattering form factors, charge density distributions and charge,neutron and matter root mean square (rms) radii for P24PMg, P28PSi and P32PS nuclei arestudied using the effect of occupation numbers. Single-particle radial wave functionsof harmonic-oscillators (HO) potential are used. In general, the results of elasticcharge form factors showed good agreement with experimental data. The occupationnumbers are taken to reproduce the quantities mentioned above. The inclusion ofoccupation numbers enhances the form factors to become closer to the data. For thecalculated charge density distributions, the results show good agreement withexperimental data except the fail to produce the hump in the central region for P28PSinucleus. Finally, the calculated charge rms radii for the nuclei under study showgood agreement with experimental data.PACS number(s): 21.60.Cs, 21.60.De, 25.30.Bf, 27.10.+h, 27.20.+n